Functional interplay between heat shock protein 90 (HSP90) and heat shock factors (HSFs) - Chakraborty, Abir; Sistonen, Lea; Roos-Mattjus, Pia (Elsevier, 2026)
Maintenance of protein homeostasis, also known as proteostasis, is essential for cellular survival under both basal and stress conditions. Proteostasis relies on a coordinated action between molecular chaperones, such as heat shock proteins (HSPs), and stress-responsive transcription factors. HSP90 is an abundant and functionally central ATP-dependent chaperone that supports the stability and function of a great variety of client proteins, while specific members of the heat shock factor (HSF) family orchestrate transcriptional programs in cells exposed to proteotoxic stress. According to the established chaperone titration model, HSP90, together with other chaperones, represses the master regulator HSF1 by maintaining it in an inactive monomeric state. Emerging evidence, however, indicates that also other HSFs, especially HSF2, can form a complex with HSP90 and contribute to constitutive and stress-inducible HSP gene regulation, thereby expanding the HSF1-centric view of the chaperone titration model. This review discusses the current understanding of the HSP90-HSF interplay and highlights the recent advances in targeting HSP90 for therapeutic purposes. Together, these insights underscore the HSP90-HSF axis as a regulatory hub of proteostasis in health and disease.